Peculiarities of existing IT-projects management methodologies in telecommunications - Калмыков, Андрей Викторович (Eastern-European Journal of Enterprise Technologies, 2012)
The article reviews peculiarities of IT-projects management in the telecommunications industry. The specificities of these tasks are shown, as well as indicators for evaluating of IT-projects management methodologies, regarding industry-specific requirements and demands, are proposed. The most well-known approaches to the development of software products (RUP, Agile, V-model), development management of complex engineering systems, industry standards and recommendations for the development and implementation of OSS, supported by Telecom Management Forum, have been considered as base initial methodologies. Also shown that these methodologies in the scope of telecommunication IT-projects (large-scale long-term and short-term) of different types are not efficient enough. At the same time, strengths of each of these approaches, their compliance to requirements of IT projects in telecommunications are defined and investigated. The most effective mechanisms and principles of the considered methods of information systems development management are offered to be used for perspective industry-specific methodology of IT projects management